FROM SCREEN TO SKILLS: INVESTIGATING CARTOONS' INFLUENCE ON PRESCHOOLERS’ DEVELOPMENT - Kabadayi, Abdülkadir (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
During the preschool period, cartoons wield a significant influence on child development across cognitive, social, emotional, and imaginative domains. These animated shows serve as platforms for learning, introducing pre-schoolers to language, numeracy, problem-solving, and emotional literacy. However, the impact of cartoons isn't uni-dimensional; they can shape behavior positively by fostering empathy and creativity, yet excessive exposure to certain content may lead to attention issues and unrealistic perceptions. Parental guidance and media literacy play pivotal roles in navigating the preschool’s cartoon landscape, enabling caregivers to facilitate discussions, monitor screen time, and foster critical thinking skills. Understanding the multifaceted effects of cartoons empowers parents and educators to harness their potential as educational tools while mitigating potential negative consequences, thereby optimizing child development during the crucial preschool years.